Sharp rates of convergence for accumulated spectrograms. (23rd October 2017) - Abreu, Luís Daniel; Pereira, João M; Romero, José Luis
Abstract: We investigate an inverse problem in time-frequency localization: the approximation of the symbol of a time-frequency localization operator from partial spectral information by the method of accumulated spectrograms (the sum of the spectrograms corresponding to large eigenvalues). We derive a sharp bound for the rate of convergence of the accumulated spectrogram, improving on recent results.